1947
DOI: 10.1021/j150452a009
|View full text |Cite
|
Sign up to set email alerts
|

Energy Additivity in Oxygen-containing Crystals and Glasses.

Abstract: In recent papers (2, 3) it has been shown that the energies of dissociation of simple and complex oxides into the gaseous ions of their component elements are approximately additive, conforming to the relationship where Ei is the "ionic dissociation energy" of the compound (or glass) M,M:,Ml,, . . * 0, and zy is a constant characteristic of element M. This constant may be thought of as the average contribution of one gram-atom of element M to the total energy of dissociation into gaseous ions of compounds or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Following their work, G i was calculated for CeO 2 from the heats of formation for crystalline CeO 2 and gaseous Ce, and the density and molecular weight of CeO 2 [27,[29][30][31][32][33][34]. The density of each CASP and CAP glass was determined by Archimedes method using kerosene as the immersion fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Following their work, G i was calculated for CeO 2 from the heats of formation for crystalline CeO 2 and gaseous Ce, and the density and molecular weight of CeO 2 [27,[29][30][31][32][33][34]. The density of each CASP and CAP glass was determined by Archimedes method using kerosene as the immersion fluid.…”
Section: Methodsmentioning
confidence: 99%
“…(2), Makishima and Mackenzie [13], Rocherulle et al [16] and Inaba et al [19] observed a good agreement between the calculated and measured Young moduli in their glasses. However, all V i values used in these literature were based on Pauling's ionic radii in octahedral coordination, and the old thermodynamic data [46,47] were adopted by some authors for their calculation of G i . Values of both V i and G i , on the other hand, have been recalculated by Lin and Liu [26], using Shannon's radii [48] with appropriate CN and the thermodynamic data listed in CRC Handbook of Chemistry and Physics (1992/1993).…”
Section: Elastic Moduli Based On the Ideal Mixing Modelmentioning
confidence: 99%
“…Kwak and Sung [19] have reported that the single bond strength of Bi-O bond is 214 kJ/mol. But according to Sun and Huggins [20] the dissociation energy of Bi 2 O 3 is 147 kcal/mol. It has been clarified from IR, Raman and X-ray diffraction analysis that coordination number of Bi 3+ does not change and remains high values of around six independent of glass composition in the Bi 2 O 3 -B 2 O 3 system [7,21].…”
Section: Introductionmentioning
confidence: 98%
“…[19] but it seems more reasonable since it is found on the basis of dissociation energy of the oxide while the value of Kwak and Sung is obtained using an approximation of relationship between bond strength and field strength of different cations. According to Sun and Huggins [20] the dissociation energy of Sb 2 O 3 is 164 kcal/mol and the single bond strength of Sb-O bond by using coordination number of Sb 3+ cation CN = 3 is 54.7 kcal/mol or 228.9 kJ/mol. Coordination number of Sb 3+ cation CN = 3 assumed in this paper is in agreement with IR and Raman spectral results reported by Terashima et al [7] as well as Sb K-edge EXAFS spectral results obtained by Ellison and Sen [22] for Sb 2 O 3 -B 2 O 3 glasses.…”
Section: Introductionmentioning
confidence: 99%